A dark-field microscope for background-free detection of resonance fluorescence from single semiconductor quantum dots operating in a set-and-forget mode - Kuhlmann, Andreas V.; Houel, Julien; Brunner, Daniel; Ludwig, Arne; Reuter, Dirk; Wieck, Andreas D.; Warburton, Richard J. (Review of Scientific Instruments)

Spin injection, transport, and relaxation in spin light-emitting diodes: magnetic field effects - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (Spintronics VI)

Spin relaxation length in quantum dot spin LEDs - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (physica status solidi (c))

Influence of recombination center interaction on the photoluminescence of AlGaAs/GaAs heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Hanle effect in (In,Ga)As quantum dots: Role of nuclear spin fluctuations - Kuznetsova, M. S.; Flisinski, K.; Gerlovin, I. Ya.; Ignatiev, I. V.; Kavokin, K. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Origins of conductance anomalies in ap-type GaAs quantum point contact - Komijani, Y.; Csontos, M.; Ihn, T.; Ensslin, K.; Meir, Y.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Grazing-incidence X-ray diffraction of single GaAs nanowires at locations defined by focused ion beams - Bussone, Genziana; Schott, Rüdiger; Biermanns, Andreas; Davydok, Anton; Reuter, Dirk; Carbone, Gerardina; Schülli, Tobias U.; Wieck, Andreas D.; Pietsch, Ullrich (Journal of Applied Crystallography)

Influence of surface states on quantum and transport lifetimes in high-quality undoped heterostructures - Wang, D. Q.; Chen, J. C. H.; Klochan, O.; Das Gupta, K.; Reuter, Dirk; Wieck, A. D.; Ritchie, D. A.; Hamilton, A. R. (Physical Review B)

Scaling of the Kondo zero-bias peak in a hole quantum dot at finite temperatures - Klochan, O.; Micolich, A. P.; Hamilton, A. R.; Reuter, Dirk; Wieck, A. D.; Reininghaus, F.; Pletyukhov, M.; Schoeller, H. (Physical Review B)

Hot carrier effects on the magneto-optical detection of electron spins in GaAs - Henn, T.; Heckel, A.; Beck, M.; Kiessling, T.; Ossau, W.; Molenkamp, L. W.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Many-body correlations of electrostatically trapped dipolar excitons - Schinner, G. J.; Repp, J.; Schubert, E.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Govorov, A. O.; Holleitner, A. W.; Kotthaus, J. P. (Physical Review B)

Optical Spectroscopy of Spin Noise - Zapasskii, V. S.; Greilich, A.; Crooker, S. A.; Li, Yan; Kozlov, G. G.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review Letters)

Confinement and Interaction of Single Indirect Excitons in a Voltage-Controlled Trap Formed Inside Double InGaAs Quantum Wells - Schinner, G. J.; Repp, J.; Schubert, E.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Govorov, A. O.; Holleitner, A. W.; Kotthaus, J. P. (Physical Review Letters)

Temperature dependence of hole spin coherence in (In,Ga)As quantum dots measured by mode-locking and echo techniques - Varwig, S.; René, A.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Aharonov–Bohm rings with strong spin–orbit interaction: the role of sample-specific properties - Nichele, F; Komijani, Y; Hennel, S; Gerl, C; Wegscheider, W; Reuter, Dirk; Wieck, A D; Ihn, T; Ensslin, K (New Journal of Physics)

On the annealing mechanism of AuGe/Ni/Au ohmic contacts to a two-dimensional electron gas in GaAs/AlxGa1−xAs heterostructures - Koop, E J; Iqbal, M J; Limbach, F; Boute, M; van Wees, B J; Reuter, Dirk; Wieck, A D; Kooi, B J; van der Wal, C H (Semiconductor Science and Technology)

Correlation and dephasing effects on the non-radiative coherence between bright excitons in an InAs QD ensemble measured with 2D spectroscopy - Moody, G.; Singh, R.; Li, H.; Akimov, I.A.; Bayer, M.; Reuter, Dirk; Wieck, A.D.; Cundiff, S.T. (Solid State Communications)

Anisotropic Zeeman shift in p-type GaAs quantum point contacts - Komijani, Y.; Csontos, M.; Shorubalko, I.; Zülicke, U.; Ihn, T.; Ensslin, K.; Reuter, Dirk; Wieck, A. D. (EPL (Europhysics Letters))

Fifth-order nonlinear optical response of excitonic states in an InAs quantum dot ensemble measured with two-dimensional spectroscopy - Moody, G.; Singh, R.; Li, H.; Akimov, I. A.; Bayer, M.; Reuter, Dirk; Wieck, A. D.; Cundiff, S. T. (Physical Review B)

Confinement Effects on Biexciton Binding in Semiconductor Quantum Dots Measured with 2D Coherent Spectroscopy - Moody, G.; Singh, R.; Li, H.; Akimov, I. A.; Bayer, M.; Reuter, Dirk; Wieck, A. D.; Bracker, A. S.; Gammon, D.; Cundiff, S. T. (CLEO: 2013)

Observation of the Kondo effect in a spin-3/2 hole quantum dot - Klochan, O.; Micolich, A.P.; Hamilton, A.R.; Trunov, K.; Reuter, Dirk; Wieck, A.D. (COMMAD 2012)

Excitons, Biexcitons, and Trions in an InAs Quantum Dot Ensemble Studied with 2D Fourier-Transform Spectroscopy - Moody, Galan; Singh, Rohan; Li, Hebin; Akimov, Ilya; Bayer, Manfred; Reuter, Dirk; Wieck, Andreas; Cundiff, Steven T. (Conference on Lasers and Electro-Optics 2012)

Coherence of Fine-Structure States of an InAs Quantum Dot Ensemble Studied with 2D Fourier-Transform Spectroscopy - Singh, R.; Moody, G.; Li, H.; Akimov, I. A.; Bayer, M.; Reuter, Dirk; Wieck, A. D.; Cundiff, S. T. (Conference on Lasers and Electro-Optics 2012)

Counting statistics of hole transfer in ap-type GaAs quantum dot with dense excitation spectrum - Komijani, Y.; Choi, T.; Nichele, F.; Ensslin, K.; Ihn, T.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Spin relaxation in spin light-emitting diodes: effects of magnetic field and temperature - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (Ultrafast Phenomena and Nanophotonics XVII)

Structural enhancement of ZnO on SiO2 for photonic applications - Ruth, Marcel; Meier, Cedrik (AIP Advances)

Surface Diffusion of 3d-Metals on W(110) - Reuter, Dirk; Gerth, Gerhard; Kirschner, J. (Surface Diffusion)

Cubic GaN quantum dots embedded in zinc-blende AlN microdisks - Bürger, M.; Kemper, R.M.; Bader, C.A.; Ruth, M.; Declair, S.; Meier, Cedrik; Förstner, Jens; As, D.J. (Journal of Crystal Growth)
Microresonators containing quantum dots find application in devices like single photon emitters for quantum information technology as well as low threshold laser devices. We demonstrate the fabrication of 60 nm thin zinc-blende AlN microdisks including cubic GaN quantum dots using dry chemical etching techniques. Scanning electron microscopy analysis reveals the morphology with smooth surfaces of the microdisks. Micro-photoluminescence measurements exhibit optically active quantum dots. Furthermore this is the first report of resonator modes in the emission spectrum of a cubic AlN microdisk.
Keywords: tet_topic_qd; tet_topic_microdisk

Whispering gallery modes in zinc-blende AlN microdisks containing non-polar GaN quantum dots - Bürger, M.; Ruth, M.; Declair, S.; Förstner, Jens; Meier, Cedrik; As, Donat Josef (Applied Physics Letters)
Whispering gallery modes (WGMs) were observed in 60 nm thin cubic AlN microdisk resonators containing a single layer of non-polar cubic GaN quantum dots. Freestanding microdisks were patterned by means of electron beam lithography and a two step reactive ion etching process. Micro-photoluminescence spectroscopy investigations were performed for optical characterization. We analyzed the mode spacing for disk diameters ranging from 2-4 lm. Numerical investigations using three dimensional finite difference time domain calculations were in good agreement with the experimental data. Whispering gallery modes of the radial orders 1 and 2 were identified by means of simulated mode field distributions.
Keywords: tet_topic_qd; tet_topic_microdisk

Cubic GaN on nano-patterned 3C-SiC/Si (001) substrates - Kemper, R.M.; As, Donald; Lindner, Jörg (Silicon-based Nanomaterials)

Colloidal nano-lithography: state-of-the-art - Brassat, Katharina; Pauly, Johannes; Kemper, R.; Strake, M.; Brodehl, Christoph; Sievers, Werner; Riedl, Thomas; Lindner, Jörg

Self-organization of nanospheres in trenches on silicon surfaces - Brassat, Katharina; Assion, Fabian; Hilleringmann, Ulrich; Lindner, Jörg (physica status solidi (a))
The selective deposition and self-assembly of nanospheres from a colloidal suspension in trenches on silicon surfaces is investigated using conventional light, confocal laser scanning and scanning electron microscopy. Trenches with widths of one to several nanosphere diameters are formed on silicon surfaces by photolithography and reactive ion etching. The spreading knife convective self-assembly technique is employed to distribute the nanosphere suspension on the pre-patterned surface. It is shown that this technique is particularly useful in combination with a functionalized surface where a selfassembled molecular monolayer changes the contact angle such that sphere deposition takes place almost exclusively in the trenches. By this, lines selectively filled with a chain of beads with a length of 0.5 mm have been achieved.

Selective deposition of nanospheres in trenches on silicon surfaces by self-organisation - Brassat, Katharina; Lindner, Jörg

Tailored structures produced via nanosphere lithography - Brodehl, Christoph; Greulich-Weber, Siegmund; Lindner, Jörg

Dewetting and Redistribution of an Au Catalyst on Nanopatterned 3C-SiC/Si (001) Surfaces - Dogan, M.; Kemper, R.M.; Lindner, Jörg

Characterization of cubic GaN/AlN multi-quantum wells using state-of-the-art analytical STEM - Lindner, Jörg; Kemper, R.M.; As, Donald; Meeertens, D.; Kovács, A.; Luysberg, M.; Tillmann, K.

Nanosphere lithography for device fabrication - Lindner, Jörg (SPIE Newsroom)

Nickel Nanodot Arrays on Silicon formed by Nanosphere Lithography: A TEM Study - Pauly, Johannes; Lindner, Jörg

Self-organized Fabrication of Periodic Nanocolumn Arrays on GaAs Surfaces - Riedl, Thomas; Lindner, Jörg

Elemental distribution, solute solubility and defect free volume in nanocrystalline restricted-equilibrium Cu–Ag alloys - Riedl, Thomas; Kirchner, A; Eymann, K; Shariq, A; Schlesiger, R; Schmitz, G; Ruhnow, M; Kieback, B (Journal of Physics: Condensed Matter)
In this article we study the elemental distribution and solute solubility in nanocrystalline alloys of immiscible components near restricted equilibrium for the case of the binary Cu–Ag system. As predicted from thermodynamic considerations, a grain boundary segregated monophase alloy is observed in the annealed mechanically alloyed state for low Ag content by using atom probe tomography. From the detected Ag solute grain boundary enrichment the segregation free enthalpy is estimated to range between -25 and -49 kJ mol^-1 following the McLean equation, in agreement with values reported for coarse-grained Cu–Ag. The extension of the alloying range is described by a two-domain thermodynamic model that considers the excess free volume in the grain boundaries and the strain in the strain interior on the basis of the universal equation of state at negative pressure. To access the grain boundary volumetric strain experimentally, a method based on a combination of density measurements and microscopical quantification of closed pore areas is presented. Moreover, we apply x-ray diffraction line broadening analysis to determine the local strain amplitude, which yields a root-mean-square microstrain of 0.3% for a grain size of 30 nm. It is shown that the grain boundary free volume represents the major origin for the global solubility enhancement in nanocrystalline Cu–Ag at 503 K.

Ion Interactions with Nanopatterned Surfaces - Lindner, Jörg

Two-photon physics with quantum-dot biexcitons - Schumacher, Stefan; Zrenner, Artur (ULTRAFAST PHENOMENA AND NANOPHOTONICS XVII)

Blue-green emitting microdisks using low-temperature-grown ZnO on patterned silicon substrates - Ruth, Marcel; Zentgraf, Thomas; Meier, Cedrik (Optics Express)

Interference-induced asymmetric transmission through a monolayer of anisotropic chiral metamolecules - Zhang, Shuang; Liu, Fu; Zentgraf, Thomas; Li, Jensen (Physical Review A)

Three-dimensional optical holography using a plasmonic metasurface - Huang, Lingling; Chen, Xianzhong; Mühlenbernd, Holger; Zhang, Hao; Chen, Shumei; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Cheah, Kok-Wai; Qiu, Cheng-Wei; Li, Jensen; Zentgraf, Thomas; et al. (Nature Communications)

Reversible Three-Dimensional Focusing of Visible Light with Ultrathin Plasmonic Flat Lens - Chen, Xianzhong; Huang, Lingling; Mühlenbernd, Holger; Li, Guixin; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Qiu, Cheng-Wei; Zentgraf, Thomas; Zhang, Shuang (Advanced Optical Materials)

Metalens with convex and concave functionality - Zhang, Shuang; Chen, Xianzhong; Huang, Lingling; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Mühlenbernd, Holger; Zentgraf, Thomas; Li, Guixin; Qiu, Cheng-Wei (SPIE Newsroom)

Helicity dependent directional surface plasmon polariton excitation using a metasurface with interfacial phase discontinuity - Huang, Lingling; Chen, Xianzhong; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Zentgraf, Thomas; Zhang, Shuang (Light: Science & Applications)

Formation and control of Turing patterns in a coherent quantum fluid - Ardizzone, Vincenzo; Lewandowski, Przemyslaw; Luk, M. H.; Tse, Y. C.; Kwong, N. H.; Lücke, Andreas; Abbarchi, Marco; Baudin, Emmanuel; Galopin, Elisabeth; Bloch, Jacqueline; Lemaitre, Aristide; Leung, P. T.; et al. (Scientific Reports)

Charge Photogeneration in Donor–Acceptor Conjugated Materials: Influence of Excess Excitation Energy and Chain Length - Tautz, Raphael; Da Como, Enrico; Wiebeler, Christian; Soavi, Giancarlo; Dumsch, Ines; Fröhlich, Nils; Grancini, Giulia; Allard, Sybille; Scherf, Ullrich; Cerullo, Giulio; Schumacher, Stefan; Feldmann, Jochen (Journal of the American Chemical Society)

Transverse optical instability patterns in semiconductor microcavities: Polariton scattering and low-intensity all-optical switching - Luk, M. H.; Tse, Y. C.; Kwong, N. H.; Leung, P. T.; Lewandowski, Przemyslaw; Binder, R.; Schumacher, Stefan (Physical Review B)

Excited-State Absorption of Conjugated Polymers in the Near-Infrared and Visible: A Computational Study of Oligofluorenes - Ling, Sanliang; Schumacher, Stefan; Galbraith, Ian; Paterson, Martin J. (The Journal of Physical Chemistry C)

Direct Observation of Sub-Binomial Light - Bartley, Tim; Donati, Gaia; Jin, Xian-Min; Datta, Animesh; Barbieri, Marco; Walmsley, Ian A. (Physical Review Letters)

Strategies for enhancing quantum entanglement by local photon subtraction - Bartley, Tim; Crowley, Philip J. D.; Datta, Animesh; Nunn, Joshua; Zhang, Lijian; Walmsley, Ian (Physical Review A)

Requirements for two-source entanglement concentration - Vidrighin, Mihai; Bartley, Tim; Donati, Gaia; Jin, Xian-Min; Barbieri, Marco; Kolthammer, W. Steven; Datta, Animesh; Walmsley, Ian A. (Quantum Measurements and Quantum Metrology)

Geometrical and optical benchmarking of copper guanidine-quinoline complexes: Insights from TD-DFT and many-body perturbation theory† - Jesser, Anton; Rohrmüller, Martin; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)

Friggeet al.Reply: - Frigge, T.; Wall, S.; Krenzer, B.; Wippermann, St.; Sanna, S.; Klasing, F.; Hanisch-Blicharski, A.; Kammler, M.; Schmidt, Wolf Gero; Horn-von Hoegen, M. (Physical Review Letters)

LiNb1-xTaxO3Electronic Structure and Optical Response fromFirst-PrinciplesCalculations - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Ferroelectrics)

Charge compensation by long-period reconstruction in strongly polar lithium niobate surfaces - Sanna, S.; Rode, S.; Hölscher, R.; Klassen, S.; Marutschke, C.; Kobayashi, K.; Yamada, H.; Schmidt, Wolf Gero; Kühnle, A. (Physical Review B)

Adsorption of PTCDA on NaCl(100) and KCl(100) - Aldahhak, Hazem; Schmidt, Wolf Gero; Rauls, E. (Surface Science)

Monolayer Doping via Phosphonic Acid Grafting on Silicon: Microscopic Insight from Infrared Spectroscopy and Density Functional Theory Calculations - Longo, Roberto C.; Cho, Kyeongjae; Schmidt, Wolf Gero; Chabal, Yves J.; Thissen, Peter (Advanced Functional Materials)

Optical response of stoichiometric and congruent lithium niobate from first-principles calculations - Riefer, Arthur; Sanna, Simone; Schindlmayr, Arno; Schmidt, Wolf Gero (Physical Review B)
The frequency-dependent dielectric function and the second-order polarizability tensor of ferroelectric LiNbO3 are calculated from first principles. The calculations are based on the electronic structure obtained from density-functional theory. The subsequent application of the GW approximation to account for quasiparticle effects and the solution of the Bethe-Salpeter equation for the stoichiometric material yield a dielectric function that slightly overestimates the absorption onset and the oscillator strength in comparison with experimental measurements. Calculations at the level of the independent-particle approximation indicate that these deficiencies are, at least, partially related to the neglect of intrinsic defects typical for the congruent material. The second-order polarizability calculated within the independent-particle approximation predicts strong nonlinear coefficients for photon energies above 1.5 eV. The comparison with measured data suggests that the inclusion of self-energy effects in the nonlinear optical response leads to a better agreement with experiments. The intrinsic defects of congruent samples reduce the optical nonlinearities, in particular, for the 21 and 31 tensor components, further improving the agreement between experiments and theory.

Structural variety of 5-fluoroarene-2-aminopyrimidine in comparison to 2-aminopyrimidine silver(i) coordination polymers: progress report and overview - Eberhard, Jens; Stoll, Ion; Brockhinke, Regina; Neumann, Beate; Stammler, Hans-Georg; Riefer, Arthur; Rauls, Eva; Schmidt, Wolf Gero; Mattay, Jochen (CrystEngComm)

Bis-μ-oxo and μ-η2:η2-peroxo dicopper complexes studied within (time-dependent) density-functional and many-body perturbation theory - Rohrmüller, M.; Herres-Pawlis, S.; Witte, M.; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Atomic Structure of Interface States in Silicon Heterojunction Solar Cells - George, B. M.; Behrends, J.; Schnegg, A.; Schulze, T. F.; Fehr, M.; Korte, L.; Rech, B.; Lips, K.; Rohrmüller, M.; Rauls, E.; Schmidt, Wolf Gero; Gerstmann, U. (Physical Review Letters)

LiNb1-xTaxO3Electronic Structure and Optical Response fromFirst-PrinciplesCalculations - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Ferroelectrics)

Analytic evaluation of the electronic self-energy in the GW approximation for two electrons on a sphere - Schindlmayr, Arno (Physical Review B)
The GW approximation for the electronic self-energy is an important tool for the quantitative prediction of excited states in solids, but its mathematical exploration is hampered by the fact that it must, in general, be evaluated numerically even for very simple systems. In this paper I describe a nontrivial model consisting of two electrons on the surface of a sphere, interacting with the normal long-range Coulomb potential, and show that the GW self-energy, in the absence of self-consistency, can in fact be derived completely analytically in this case. The resulting expression is subsequently used to analyze the convergence of the energy gap between the highest occupied and the lowest unoccupied quasiparticle orbital with respect to the total number of states included in the spectral summations. The asymptotic formula for the truncation error obtained in this way, whose dominant contribution is proportional to the cutoff energy to the power −3/2, may be adapted to extrapolate energy gaps in other systems.

Zur Handlungsvalidität von Tests zum professionellen Wissen von Lehrkräften - Vogelsang, Christoph; Reinhold, Peter (Zeitschrift für Didaktik der Naturwissenschaften)

Experimental Observation of the Spectral Gap in Microwave n-Disk Systems - Barkhofen, Sonja; Weich, Tobias; Potzuweit, A.; Stöckmann, H.-J.; Kuhl, U.; Zworski, M. (Physical Review Letters)
Keywords: General Physics and Astronomy

Qualität inklusiven Unterrichts in der Grundschule. Symposium auf der Tagung „Gemeinsam anders lehren und lernen – Wege in die inklusive Bildung“. Gemeinsame Jahrestagung der DGfE Kommission Grundschulforschung und Didaktik der Primarstufe und der DGfE Sektion Sonderpädagogik - Hellmich, Frank; Blumberg, Eva

Coherent control of interaction and entanglement of a Rydberg atom with few photons - Sharapova, Polina; Tikhonova, O V (Laser Physics Letters)
Keywords: Physics and Astronomy (miscellaneous); Instrumentation

Time-to-space conversion of ultrafast waveforms at 155 μm in a planar periodically poled lithium niobate waveguide - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Post-selection free, integrated optical source of non-degenerate, polarization entangled photon pairs - Herrmann, Harald; Yang, Xu; Thomas, Abu; Poppe, Andreas; Sohler, Wolfgang; Silberhorn, Christine (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

A versatile source of single photons for quantum information processing - Förtsch, Michael; Fürst, Josef U.; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Chekhova, Maria V.; Silberhorn, Christine; Leuchs, Gerd; Marquardt, Christoph (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Increasing the Dimensionality of Quantum Walks Using Multiple Walkers - Rohde, Peter P.; Schreiber, Andreas; Štefaňák, Martin; Jex, Igor; Gilchrist, Alexei; Silberhorn, Christine (Journal of Computational and Theoretical Nanoscience)
Keywords: Electrical and Electronic Engineering; Computational Mathematics; Condensed Matter Physics; General Materials Science; General Chemistry

Spatio-spectral characteristics of parametric down-conversion in waveguide arrays - Kruse, R; Katzschmann, F; Christ, A; Schreiber, A; Wilhelm, S; Laiho, K; Gábris, A; Hamilton, C S; Jex, I; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Femtosecond quantum interference control of electrical currents in GaAs: Signatures beyond the perturbative χ(3) limit - Sternemann, E.; Jostmeier, T.; Ruppert, C.; Duc, H. T.; Meier, Torsten; Betz, M. (Physical Review B)

Newton's cradles in optics: From N-soliton fission to soliton chains - Driben, R.; Malomed, B.A.; Yulin, A. V.; Skryabin, D.V. (Physical Review A)
A mechanism for creating a Newton's cradle (NC) in nonlinear light wave trains under the action of the third-order dispersion (TOD) is demonstrated. The formation of the NC structure plays an important role in the process of fission of higher-order (N) solitons in optical fibers. After the splitting of the initial N soliton into a nonuniform chain of fundamental quasisolitons, the tallest one travels along the entire chain, through consecutive collisions with other solitons, and then escapes, while the remaining chain of pulses stays as a bound state, due to the radiation-mediated interaction between them. Increasing the initial soliton's order, N, leads to the transmission through, and release of additional solitons with enhanced power, along with the emission of radiation, which may demonstrate a broadband supercontinuum spectrum. The NC dynamical regime remains robust in the presence of extra perturbations, such as the Raman and self-steepening effects, and dispersion terms above the third order. It is demonstrated that essentially the same NC mechanism is induced by the TOD in finite segments of periodic wave trains (in particular, soliton chains). A difference from the mechanical NC is that the TOD-driven pulse passing through the soliton array collects energy and momentum from other solitons. Thus, uniform and nonuniform arrays of nonlinear wave pulses offer an essential extension of the mechanical NC, in which the quasiparticles, unlike mechanical beads, interact inelastically, exchanging energy and generating radiation. Nevertheless, the characteristic phenomenology of NC chains may be clearly identified in these nonlinear-wave settings too.

Instabilities, solitons and rogue waves in PT-coupled nonlinear waveguides - Bludov, Y.V.; Driben, R.; Konotop, V.V.; Malomed, B.A. (Journal of Optics)
We considered the modulational instability of continuous-wave backgrounds, and the related generation and evolution of deterministic rogue waves in the recently introduced parity–time (P T)-symmetric system of linearly coupled nonlinear Schrödinger equations, which describes a Kerr-nonlinear optical coupler with mutually balanced gain and loss in its cores. Besides the linear coupling, the overlapping cores are coupled through the cross-phase-modulation term too. While the rogue waves, built according to the pattern of the Peregrine soliton, are (quite naturally) unstable, we demonstrate that the focusing cross-phase-modulation interaction results in their partial stabilization. For P T-symmetric and antisymmetric bright solitons, the stability region is found too, in an exact analytical form, and verified by means of direct simulations

Generation of tightly compressed solitons with a tunable frequency shift in Raman-free fibers - Driben, R.; Malomed, B.A. (Optics Letters)
Optimization of the compression of input 𝑁 -solitons into robust ultra-narrow fundamental solitons, with a tunable up- or downshifted frequency, is proposed in photonic crystal fibers free of the Raman effect. Due to the absence of the Raman self-frequency shift, these fundamental solitons continue propagation, maintaining the acquired frequency, once separated from the input 𝑁 soliton’s temporal slot. A universal optimal value of the relative strength of the third-order dispersion is found, providing the strongest compression of the fundamental soliton is found. It depends only on the order of the injected 𝑁 -soliton. The largest compression degree significantly exceeds the analytical prediction supplied by the Satsuma–Yajima formula. The mechanism behind this effect, which remains valid in the presence of the self-steepening, is explained.

Trapping of light in solitonic cavities and its role in the supercontinuum generation - Driben, R.; Yulin, A. V.; Efimov, A.; Malomed, B.A. (Optics Express)
We demonstrate that the fission of higher-order N-solitons with a subsequent ejection of fundamental quasi-solitons creates cavities formed by a pair of solitary waves with dispersive light trapped between them. As a result of multiple reflections of the trapped light from the bounding solitons which act as mirrors, they bend their trajectories and collide. In the spectral domain, the two solitons receive blue and red wavelength shifts, and the spectrum of the trapped light alters as well. This phenomenon strongly affects spectral characteristics of the generated supercontinuum. Consideration of the system's parameters which affect the creation of the cavity reveals possibilities of predicting and controlling soliton-soliton collisions induced by multiple reflections of the trapped light.

Inversion and tight focusing of Airy pulses under the action of third-order dispersion - Driben, R.; Hu, Y.; Chen, Z.; Malomed, B.A.; Morandotti, R. (Optics Letters)
By means of direct simulations and theoretical analysis, we study the nonlinear propagation of truncated Airy pulses in an optical fiber exhibiting both anomalous second-order and strong positive third-order dispersions (TOD). It is found that the Airy pulse first reaches a finite-size focal area as determined by the relative strength of the two dispersion terms, and then undergoes an inversion transformation such that it continues to travel with an opposite acceleration. The system notably features tight focusing if the TOD is a dominant factor. These effects are partially reduced by Kerr nonlinearity.

Nonlinear modes in binary bosonic condensates with pseudo–spin-orbital coupling - Zezyulin, D.A.; Driben, R.; Konotop, V.V.; Malomed, B.A. (Physical Review A)
We consider an effectively one-dimensional binary Bose-Einstein condensate (BEC) with nonlinear repulsive interactions and linear spin-orbit (SO) and Zeeman-splitting couplings. In the presence of the trapping harmonic-oscillator (HO) potential, we report the existence of even, odd, and asymmetric spatial modes. They feature alternating domains with opposite directions of the pseudospin, i.e., antiferromagnetic structures, which is explained by the interplay of the linear couplings, HO confinement, and repulsive self-interaction. The number of the domains is determined by the strength of the SO coupling. The modes are constructed analytically in the weakly nonlinear system. The dynamical stability of the modes is investigated by means of the Bogoliubov–de Gennes equations and direct simulations. A notable result is that the multi-domain-wall (DW) structures are stable, alternating between odd and even shapes, while the simplest single-DW structure is unstable. Thus, the system features a transition to the complex ground states under the action of the SO coupling. The addition of the Zeeman splitting transforms the odd modes into asymmetric ones via spontaneous symmetry breaking. The results suggest possibilities for switching the binary system between states with opposite (pseudo)magnetization by external fields, and realization of similar stable states and dynamical effects in solid-state and nonlinear-optical settings emulated by the SO-coupled BECs.

Soliton interaction mediated by cascaded four wave mixing with dispersive waves - Yulin, A. V.; Driben, R.; Malomed, B.A.; Skryabin, D.V. (Optics Express)
We demonstrate that trapping of dispersive waves between two optical solitons takes place when resonant scattering of the waves on the solitons leads to nearly perfect reflections. The momentum transfer from the radiation to solitons results in their mutual attraction and a subsequent collision. The spectrum of the trapped radiation can either expand or shrink in the course of the propagation, which is controlled by arranging either collision or separation of the solitons.

Collective effects in second-harmonic generation from split-ring-resonator arrays - Niesler, Fabian B.; Linden, Stefan; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, Martin (Conference on Lasers and Electro-Optics 2012)
We perform experiments on resonant second-harmonic generation from planar gold split-ring-resonator arrays under normal incidence of light as a function of the lattice constant. Optimum nonlinear conversion occurs at intermediate lattice constants.
Keywords: tet_topic_shg; tet_topic_meta

Optimal second-harmonic generation in split-ring resonator arrays - Grynko, Yevgen; Meier, Torsten; Linden, Stefan; Niesler, Fabian B. P.; Wegener, Martin; Förstner, Jens (Ultrafast Phenomena and Nanophotonics XVII)
Previous experimental measurements and numerical simulations give evidence of strong electric and magnetic field interaction between split-ring resonators in dense arrays. One can expect that such interactions have an influence on the second harmonic generation. We apply the Discontinuous Galerkin Time Domain method and the hydrodynamic Maxwell-Vlasov model to simulate the linear and nonlinear optical response from SRR arrays. The simulations show that dense placement of the constituent building blocks appears not always optimal and collective effects can lead to a significant suppression of the near fields at the fundamental frequency and, consequently, to the decrease of the SHG intensity. We demonstrate also the great role of the symmetry degree of the array layout which results in the variation of the SHG efficiency in range of two orders of magnitude.
Keywords: tet_topic_shg; tet_topic_meta

Selection rules and linear absorption spectra of carbon nanotubes in axial magnetic fields - Liu, Hong; Schumacher, Stefan; Meier, Torsten (Physical Review B)
We derive a transparent and easy-to-use analytic expression for the selection rules and the optical dipole matrix elements for carbon nanotubes of arbitrary chirality in the presence of axial magnetic fields using a single-orbital π-electron tight-binding model. From this, we calculate the linear absorption spectrum for arbitrary polarization directions of the incident light, providing insight into all optically allowed transition. We show that the transverse absorption peaks can be selectively excited with circularly polarized light and spectrally resolved in an axial magnetic field.

Innere Struktur und Operationalisierung Fachdidaktischen Wissens - Gramzow, Yvonne; Riese, Josef; Reinhold, Peter (Inquiry-based Learning – Forschendes Lernen)

Modellierung fachdidaktischen Wissens angehender Physiklehrkräfte - Gramzow, Yvonne; Riese, Josef; Reinhold, Peter (ZfDN (Zeitschrift für Didaktik der Naturwissenschaften))

Professional knowledge of physics student teachers – ProfiLe-P - Riese, Josef; Borowski, Andreas; Fischer, Hans E.; Gramzow, Yvonne; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst; Tomczyszyn, Elisabeth; Walzer, Martin (KoKoHs Working Papers 3)

Fachwissen Physik – Innere Struktur und Faktoren des Wissenserwerbs - Woitkowski, David; Riese, Josef; Reinhold, Peter (Inquiry-based Learning – Forschendes Lernen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Hannover 2012)

Wirksamkeit der Physiklehrerausbildung in Österreich - Krumphals, Ingrid; Riese, Josef; Hopf, Martin; Reinhold, Peter (Inquiry-based Learning – Forschendes Lernen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Hannover 2012)

Vibrational Fingerprints of LiNbO3-LiTaO3Mixed Crystals - Sanna, Simone; Riefer, A.; Neufeld, Sergej; Schmidt, Wolf Gero; Berth, Gerhard; Rüsing, Michael; Widhalm, A.; Zrenner, Artur (Ferroelectrics)
Atomistic simulations in the framework of the density functional theory have been used to model morphologic and vibrational properties of lithium niobate–lithium tantalate mixed crystals as a function of the [Nb]/[Ta] ratio. Structural parameters such as the crystal volume and the lattice parameters a and c vary roughly linearly from LiTaO3 to LiNbO3, showing only minor deviations from the Vegard behavior. Our ab initio calculations demonstrate that the TO1, TO2 and TO4 vibrational modes become harder with increasing Nb concentration. TO3 becomes softer with increasing Nb content, instead. Furthermore, the investigated zone center A1 -TO phonon modes are characterized by a pronounced stoichiometry dependence. Frequency shifts as large as 30 cm−1 are expected as the [Nb]/[Ta] ratio grows from 0 to 1. Therefore, spectroscopic techniques sensitive to the A1 modes (such as Raman spectroscopy), can be employed for a direct and non-destructive determination of the crystal composition.
Keywords: Ferroelectrics; vibrational properties; LiNbO3; LiTaO3; mixed crystals

Transition energies and direct-indirect band gap crossing in zinc-blende AlxGa1−xN - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero; Röppischer, Marcus; Cobet, Christoph; Esser, Norbert; Schupp, Thorsten; As, Donat J.; Feneberg, Martin; Goldhahn, Rüdiger (Physical Review B)

CuO and Co3O4 Nanoparticles: Synthesis, Characterizations, and Raman Spectroscopy - Rashad, M.; Rüsing, Michael; Berth, Gerhard; Lischka, K.; Pawlis, A. (Journal of Nanomaterials)
Copper oxide and cobalt oxide (CuO, Co3O4) nanocrystals (NCs) have been successfully prepared in a short time using microwave irradiation without any postannealing treatment. Both kinds of nanocrystals (NCs) have been prepared using copper nitrate and cobalt nitrate as the starting materials and distilled water as the solvent. The resulted powders of nanocrystals (NCs) were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and atomic force microscopy (AFM) measurements. The obtained results confirm the presence of the both of oxides nanopowders produced during chemical precipitation using microwave irradiation. A strong emission under UV excitation is obtained from the prepared CuO and Co3O4 nanoparticles. The results show that the nanoparticles have high dispersion and narrow size distribution. The line scans of atomic force microscopy (AFM) images of the nanocrystals (NCs) sprayed on GaAs substrates confirm the results of both X-ray diffraction and transmission electron microscopy. Furthermore, vibrational studies have been carried out using Raman spectroscopic technique. Specific Raman peaks have been observed in the CuO and Co3O4 nanostructures, and the full width at half maximum (FWHM) of the peaks indicates a small particle size of the nanocrystals.
Keywords: General Materials Science

Hybrid functionals and GW approximation in the FLAPW method - Friedrich, Christoph; Betzinger, Markus; Schlipf, Martin; Blügel, Stefan; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
We present recent advances in numerical implementations of hybrid functionals and the GW approximation within the full-potential linearized augmented-plane-wave (FLAPW) method. The former is an approximation for the exchange–correlation contribution to the total energy functional in density-functional theory, and the latter is an approximation for the electronic self-energy in the framework of many-body perturbation theory. All implementations employ the mixed product basis, which has evolved into a versatile basis for the products of wave functions, describing the incoming and outgoing states of an electron that is scattered by interacting with another electron. It can thus be used for representing the nonlocal potential in hybrid functionals as well as the screened interaction and related quantities in GW calculations. In particular, the six-dimensional space integrals of the Hamiltonian exchange matrix elements (and exchange self-energy) decompose into sums over vector–matrix–vector products, which can be evaluated easily. The correlation part of the GW self-energy, which contains a time or frequency dependence, is calculated on the imaginary frequency axis with a subsequent analytic continuation to the real axis or, alternatively, by a direct frequency convolution of the Green function G and the dynamically screened Coulomb interaction W along a contour integration path that avoids the poles of the Green function. Hybrid-functional and GW calculations are notoriously computationally expensive. We present a number of tricks that reduce the computational cost considerably, including the use of spatial and time-reversal symmetries, modifications of the mixed product basis with the aim to optimize it for the correlation self-energy and another modification that makes the Coulomb matrix sparse, analytic expansions of the interaction potentials around the point of divergence at k=0, and a nested density and density-matrix convergence scheme for hybrid-functional calculations. We show CPU timings for prototype semiconductors and illustrative results for GdN and ZnO.

Origin of gate hysteresis inp-type Si-doped AlGaAs/GaAs heterostructures - Burke, A. M.; Waddington, D. E. J.; Carrad, D. J.; Lyttleton, R. W.; Tan, H. H.; Reece, P. J.; Klochan, O.; Hamilton, A. R.; Rai, A.; Reuter, Dirk; Wieck, A. D.; Micolich, A. P. (Physical Review B)

Magnetic field dependence of the spin relaxation length in spin light-emitting diodes - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (Applied Physics Letters)

Hole spin precession in a (In,Ga)As quantum dot ensemble: From resonant spin amplification to spin mode locking - Varwig, S.; Schwan, A.; Barmscheid, D.; Müller, C.; Greilich, A.; Yugova, I. A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Transverse rectification in density-modulated two-dimensional electron gases - Ganczarczyk, A.; Rojek, S.; Quindeau, A.; Geller, M.; Hucht, A.; Notthoff, C.; König, J.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Physical Review B)